ECONOMIC EMPOWERMENT THROUGH OYSTER MUSHROOM CULTIVATION IN BUNUTIN VILLAGE, BANGLI REGENCY - Ida Ayu Candrika Dewi (International Conference on Multidisciplinary Research Perspective, 2025)
The agricultural sector in Bali is not only dominated by commodities such as rice, horticulture, and plantation crops but has also begun to develop toward modern agribusiness, one of which is the cultivation of oyster mushrooms (Pleurotus ostreatus). This study aims to analyze the role of oyster mushroom cultivation in enhancing the economic empowerment of the community in Bunutin Village, Bangli Regency. The background of this research stems from the condition of rural communities that largely depend on conventional agricultural sectors with relatively low income levels. Through the development of oyster mushroom cultivation, the community is encouraged to innovate in managing local resources productively and sustainably.The research method used is a qualitative descriptive approach, with data collection techniques including interviews, observations, and documentation involving oyster mushroom farmers, farmer group leaders, and village government officials. The data obtained were analyzed using data reduction, data presentation, and conclusion-drawing techniques.The results show that the oyster mushroom cultivation program in Bunutin Village has had a significant impact on increasing community income, expanding employment opportunities, and strengthening the entrepreneurial capacity of local farmers. This activity has also raised community awareness of the importance of agricultural diversification and the utilization of agricultural waste as an environmentally friendly growing medium. Furthermore, the support from the village government and assistance from academic institutions have contributed to strengthening the sustainability of this program.Thus, oyster mushroom cultivation has proven to be an effective strategy for economic empowerment in rural communities, particularly in Bali, which possesses favorable agroclimatic potential. Further development is expected to include business management training, innovation in processed mushroom products, and broader market access to create an independent and competitive village economy.